Conditional effects of tides and waves on short‐term marsh sedimentation dynamics. Issue 10 (24th March 2018) - Ma, Zhigang; Ysebaert, Tom; van der Wal, Daphne; Herman, Peter M.J.
Abstract : Key findings : 1. SSC was significantly correlated with wind speed during sampling. 2. Sediment deposition rates (TTD and FTD) and retention ratio (FTD/TTD) were significantly correlated with cumulative wave energy during the measurement period. 3. It is important to incorporate local sediment dynamics when evaluating marsh vulnerability and stability.